Anisotropic alteration of scleral birefringence to uniaxial mechanical strain. - Satoko Nagase; Masahiro Yamanari; Ryosuke Tanaka; Takeshi Yasui; Masahiro Miura; Takuya Iwasaki; Hiroshi Goto; Yoshiaki Yasuno (PLoS ONE, 2013)
PURPOSE: To investigate the relationship between scleral mechanical properties, its birefringence, and the anisotropy of birefringence alteration in respect of the direction of the strain by using PS-OCT. METHODS: The scleral birefringence of thirty-nine porcine eyes was measured with a prototype PS-OCT. A rectangle strip of sclera with a width of 4 mm was dissected at the temporal region 5 mm apart from the optic nerve head. The strain and force were measured with a uniaxial tension tester as the sample was stretched with a speed of 1.8 mm/min after preconditioning. The birefringence of the sample was measured by PS-OCT at the center of the sample before applying, denoted as inherent birefringence, and after applying stretching of 6.5% strain. The birefringence alteration was obtained by these two measurements and correlations between birefringence and elastic parameters, tangent modulus, and structural stiffness were examined. Twenty and 19 porcine eyes were stretched in meridional or equatorial directions, respectively. RESULTS: A moderate positive correlation was found between the inherent birefringence and the structural stiffness. A moderate positive correlation was also found between the inherent birefringence and the tangent modulus. The birefringence increased by strains. Marginal significance was found in the birefringence alteration between meridional and equatorial strains, where the mean birefringence elevation by meridional strain was higher than that by equatorial strain. CONCLUSIONS: The birefringence was found to be altered by applying strain and also be related with inherent birefringence. This implies the birefringence of the sclera of the in vivo eye also could be affected by its mechanical property.